BODY IMAGE PERCEPTIONS OF ADOLESCENTS AND THEIR RELATION SHIP TO SELF ESTEEM - K.MAYURI, V.DIVYA and (The Journal of Research, PJTSAU, 2017)
Adolescence is a critical period of growth and emotional turmoil. During adolescence period self perception about their appearance is important to thedevelopment of self esteem. Physical appearance has become one of the major concerns among adolescents, because physical changes during puberty may cause them to have both positive and negative feelings towards their body and these feelings in turn influences how they feel about themselves,leading to a sense of self worth or self esteem. Though there are many factors that influence adolescents’ self esteem, body image is one critical factor (Paxton et al. 2006).